APLIKASI TEORI PERILAKU MANAJEMEN PADA BANK MILIK PEMERINTAH DI INDONESIA - Chaerani Nisa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
This paper analyzed the behavior management in state owned bank in Indonesia. The behavior management, which is divided into four hypothesis which are, bad management, bad luck, skimping and moral hazard. This hypothesis is tested using four variables, which are efficiency, non-performing loan and capital adequacy ratio. Meanwhile, the Granger Causality test is using to find out which behavior management is happened. This concept then applied in ordinary least square model. As modification, this research use VAR (Vector Autoregressive). Since VAR also using granger causality basic concept. The result show that bad luck hypothesis happened. This is similar with the condition in India, Nordic, Central and Eastern Europe.